(untitled) (Conference Zone, 2022)
It is known from the history of the development of human society that the maturity of a child’s personality is formed in the family. The family is a very important hearth that advances the life of society, raises it to higher levels, makes it prosperous, educates and brings up the future generations, and is responsible for their development. It is the social, moral and legal duty of every parent to see a child, bring him up, and raise him to be a person capable of serving people and society honestly. Realizing this duty and fulfilling it honestly is both a duty and a duty for parents.